Modeling and Simulation of a Carrier-based PWM Voltage Source Inverter for a Nine Phase Induction Machine Drive - Omonowo David Momoh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
The analysis of a carrier-based PWM two level voltage source inverter for a nine phase induction machine drive system is presented in this paper. Methods for generating zero-sequence signals during balanced and unbalanced condition are established. Simulation results for the analysis are presented. Two fault conditions involving the voltage source inverter and the nine-phase squirrel cage induction machine load are investigated. For the two fault scenarios considered, the effects on the performance characteristics of the induction machine load are highlighted. The simulation results obtained show that the two imbalance conditions considered result in substantial oscillations on the electromagnetic torque of the machine with attendant reduction in the torque rating. There is also large slip in the rotor speed.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.6175